Cambio tecnológico y crecimiento económico - Simone, Dante (1965)
The work consists of three parts, i.e.: introduction, typology of the technological change, and study of the innovation in postkeynesian models. In the introduction, is analyzed the role of technology in the dynamics of the classics Mark, Schumpeter, Hansen, etc. Later on, and aiming to get a theoretical basis for the understanding of the innovational dynamism, the contributions of Hicks, Robinson and Harrod on this matter, are studied. The study culminates with the treatment of the postkeynesian models of Meade, Solow and Harrod. Studying this last model, emphasize is made on the supposed dissociation between the natural and the warranted rate. It pretends to demonstrate that with a function of lineal and homogeneous production, normal isoquantas, elasticity of unitarian substitution, and a constant capital coefficient (neutral innovation), such dissociation does not exist, and that rupture problems in the way of balanced expansion, will appear in the measure in which the type of innovational dynamism changes, or by divergences between the actual and warranted rate of growth.